EFFECT OF DIFFERENT PROTEIN LEVELS ON THE GROWTH AND FEED EFFICIENCY OF SILVER BARB (Barbodes gonionotus) IN FERTILIZED PONDS - Mas Tri Djoko Sunarno (Indonesian Fisheries Research Journal, 2002)
This study proposed to establish a suitable protein level in feed formulation for silver barb in a semi-intensive pond.